PEMANFAATAN KULIT BUAH SEEBAGAI PUPUK CAIR DENGAN VARIASI SUMBER GULA DAN KONSENTRASI EM4 - Septiansah, Yoga Ferdy; Kurniawan, Wahyu; Sudiro; Rahman, Nanik Astuti (Teknik Kimia ITN Malang, 2025)
Liquid organic fertilizer is one type of fertilizer that is widely circulated in the community which is produced from the fermentation of leaf waste or animal waste. This study aims to utilize fruit waste as a production material for making Liquid Organic Fertilizer (POC), in addition to determining the effectiveness of variations in sugar sources and EM4 concentrations on the quality of the POC produced. The production process of liquid organic fertilizer in this study used types of sugar with variations of granulated sugar, brown sugar, mixed sugar (granulated sugar + brown sugar) and without sugar and EM4 bioactivator concentrations of 10%, 20%, 30%, 40% and 50%. The results obtained from the nitrogen analysis ranged from 0.1-0.3 which when associated with the SNI POC did not meet the standard. Liquid organic fertilizer was obtained from testing the phosphorus content in 30% brown sugar, which was 0.00931. While the best potassium content analysis results were found in the EM4 10% granulated sugar variation sample with a result of 0.30%.